PENGARUH EXPERIENTIAL MARKETING DAN CONSUMER EXPERIENCE TERHADAP BRAND LOYALTY MELALUI BRAND TRUST SEBAGAI VARIABEL INTERVENING (STUDY PADA INUL VIZTA SEMARANG) - Herdini Sarastiti; Naili Farida; Ngatno Ngatno (Universitas Diponegoro, 2015)
This research is motivated by the phenomenon of karaoke as a lifestyle trend today. The more places that offer karaoke variety of services and facilities complete with modern technology to pamper consumers accompanied with the package offers a varied and competitive prices. The offer is aimed to attract people like a big city of Semarang. One of the karaoke placed in the city of Semarang is Inul Vizta. Inul Vizta Semarang trying to increase the number of visitors, but from 2011 to 2013 a decline in the number of visitors. The purpose of this study was to determine the influence of experiential marketing and consumer experience on brand loyalty through brand trust on Inul Vizta Semarang. The type of this research is explanatory research, with data collecting technique by questionnaire and interview. The sampling technique of this research use purposive sampling. The sample in this research were 100 respondents who were Inul Vizta Semarang’s consumer. Both quantitative analysis of this research technique using a validity test, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, a signification test (t test), path analysis and sobel test. The results of research shows that experiential marketing and consumer experience in partial positive influence on the brand of trust, experiential marketing and consumer experience a partial influence positive brand loyalty, brand trust influential positive brand loyalty, as well as experiential marketing and consumer experience a partial influence positive brand loyalty through the brand trust. Based on the analysis of test track and sobel show that the variable brand trust is variable intervening against the brand loyalty in this research.